2006
DOI: 10.1007/s00467-006-0143-1
|View full text |Cite
|
Sign up to set email alerts
|

Urinary aquaporin-2 excretion during early human development

Abstract: This study was undertaken to assess one of the determinants of kidney concentrating capacity, aquaporin-2 (AQP2), in order to understand the physiopathology of water balance in newborn babies. Urinary AQP2 excretion has been shown to be proportional to AQP2 level in the apical plasma membrane of the kidney collecting ducts and has been suggested as a marker of vasopressin (AVP) action. Urinary AQP2 excretion in the early postnatal period and at 3 weeks of age was measured in 123 neonates admitted during a 6-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…In a human study involving newborn preterm and term infants, Nyul et al detected no relationship between AQP2 excretion and urine osmolality [11]. Previous data published by our group [12] also suggest that AQP2 excretion may not be used as a direct marker of the renal AVP activity and of the capacity to concentrate urine in preterm newborns during the early postnatal adaptation to extra-uterine life.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In a human study involving newborn preterm and term infants, Nyul et al detected no relationship between AQP2 excretion and urine osmolality [11]. Previous data published by our group [12] also suggest that AQP2 excretion may not be used as a direct marker of the renal AVP activity and of the capacity to concentrate urine in preterm newborns during the early postnatal adaptation to extra-uterine life.…”
Section: Discussionmentioning
confidence: 78%
“…The level of AQP2 in the urine was measured by dotimmunoblotting, as previously described [12]. A 100-to 300-μL urine sample was applied to a nitrocellulose membrane (pore size 0.45 μm, Trans-Blot Transfer Medium; Bio-Rad, Hercules, CA) using a Bio-Dot microfiltration apparatus (Bio-Rad).…”
Section: Measurement Of Aqp2 Urinary Excretionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquaporin-2 metabolism in the fetus and neonate is not fully understood. Researches in both preterm and at term infants suggested that in early postnatal life aquaporin-2 urinary levels cannot serve as a marker of AVP renal action and renal capacity to concentrate urine (Nyul et al, 2002;Zelenina et al, 2006) although opposing results were reported (Iacobelli et al, 2006). Nevertheless, in the same studies urinary aquaporin-2 concentrations correlated adequately with the overall maturity of tubular renal function and decreased in conditions of impaired kidney activity.…”
Section: Fetal Disorders/conditions Associated With Disturbances In Amentioning
confidence: 91%
“…The measurements were repeated on eight 'standard' samples that were run with each set of patient samples to confirm the reliability of the results. 26 The final angiotensinogen concentration was expressed in micrograms per gram of urinary creatinine (µg/g uCr).…”
Section: Urine Sample Collection and Measurementmentioning
confidence: 99%